Evaluasi Kebijakan Sistem Informasi Administrasi Kependudukan (SIAK) di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Semarang - Adriyanto, Tri; Kismartini, Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Administration Information System (SIAK) is a system of information and communication technologies that facilitating the management of information on population administration in the Operator level and the Department of Population and Civil Registration as a single unit with the hope to improve the quality of population data that can be utilized to the maximum. The purpose of this study was to evaluate the implementation of SIAK in the Department of Population and Civil Registration of Semarang district along with the obstacles in its implementation. This study uses the approach of measuring the policy evaluation with four indicators: Input, Process, Output, and Outcome. This study uses descriptive qualitative research. Data collection techniques used in this study by the method of field studies (interviews, observation and documentation). The results showed that the assessment of the implementation of the policy in terms of Process Input, Output, and the outcome was appropriate and running well. Barriers contained in the implementation SIAK in the Department of Population and Civil Registration of Semarang district related to the amount of human resources are lacking, the adequacy of the network bandwidth is limited, the budget absorption is still low, the data anomalies and duplicate data in the database is large enough, to socialize in the community do not routinely do